Impact of Perioperative Multiple Doses of Glucocorticoids on Peripheral Blood Lymphocyte Subsets and Inflammatory Cytokines in Patients With Non-small Cell Lung Cancer - Yang, Liuquan; Cai, Yixin; Fu, Xiangning (Frontiers in Surgery, 2022)
Abstract Purpose: Surgery-induced immunosuppression is associated with infectious complications and cancer recurrence. This study aimed to characterize the effects of perioperative multiple doses of glucocorticoids on the peripheral immune environment in patients with non-small cell lung cancer. Methods: In this retrospective study, surgical patients with lung cancer were included. Lymphocyte subsets, lymphocyte phenotypes, lymphocyte functions, and inflammatory cytokines were evaluated in the peripheral blood preoperatively, then at 1 day and 7 days postoperatively. Levels of immune cells and inflammatory factors were compared between those who did or did not receive glucocorticoids at all time points. Results: Examination of trends over time revealed that all immune cells and inflammatory cytokines significantly altered in response to surgery at 1 day postoperatively and could not completely return to preoperative levels at 7 days postoperatively. Multiple doses or high doses (15-20 mg dexamethasone equivalents) of glucocorticoids that were all given within 24 hours were associated with decreased absolute numbers of T cells, CD4+and CD8+T cells, B cells, and impaired T cells function at 1 day postoperatively while a single intraoperative low dose (5 mg) of dexamethasone had little influence on the peripheral environment. Conclusions: Among patients with lung cancer, perioperative multiple doses of glucocorticoids that are all given within a short time are associated with decreased immune cell counts and impaired T cells functions.